Prognostic value of the mitogen response in the interferon-γ release assay in patients with culture-confirmed tuberculosis. (October 2019) - Huang, Chun-Ta; Lee, Meng-Rui; Ruan, Sheng-Yuan; Tsai, Yi-Ju; Wang, Jann-Yuan; Yu, Chong-Jen
Abstract: Background: _ The mitogen response in interferon-γ(IFN-γ) release assays(IGRAs) measures IFN-γ after binding to CD2, a surface adhesion marker found on T-cells and NK cells. A lower mitogen response implies either peripheral blood mononuclear cells have fewer adhesion molecules either in absolute numbers or per T-cells, or the pathway from adhesion molecules to IFN-γ production is not functioning well. To date, it remains poorly understood whether the mitogen response is associated with outcomes in tuberculosis patients. Methods: _ From 2012 to 2017, patients with culture-confirmed tuberculosis were tested for QuantiFERON-TB Gold In-Tube(QFT-GIT). The associations between patient outcomes and QFT-GIT as well as IFN-γ responses to the mitogen were investigated. Outcomes of interest included 1-year mortality after tuberculosis diagnosis and 2-month culture conversion. Results: _ In total, 466 culture-confirmed tuberculosis patients were enrolled and QFT-GIT was positive in 309(66%). Within 1 year of diagnosis, 20(4%) died and notably, 15(11%) out of 137 patients with a lower mitogen response did so. The multivariate Cox model showed that a lower mitogen response (hazard ratio, 8.789; 95% confidence interval, 3.074–25.129) was independently associated with 1-year mortality. Moreover, among 160 patients with smear-positive culture-confirmed pulmonary tuberculosis, multivariate logistic analysis indicated that a lower mitogen response (odds ratio, 3.966; 95% confidence interval, 1.182–13.303) was significantly associated with 2-month culture persistence. Conclusions: _ This study found that a lower mitogen response was associated with worse 1-year survival in tuberculosis patients and correlated with 2-month culture persistence in patients with sputum smear-positive culture-confirmed tuberculosis. These findings suggest another application of QFT-GIT for prognostication of tuberculosis patients. Highlights: About two-thirds of culture-confirmed TB patients were tested positive for the QFT-GIT assay. A lower Mitogen response was significantly associated with a higher hazard of 1-year mortality in TB patients. Culture persistence at 2 months was more likely observed in smear-positive pulmonary TB patients with lower Mitogen response.